Internet and computer addiction: “new age” disease of the 21st century - Vedrana Joksimović (Биомедицинска истраживања, 2015)
The aim of this paper is to give a brief overview of research and the newesttheoretical considerations on internet addiction classification and treatment.Over the past years we have been increasingly facing the so-called “newage” disease of internet addiction as a serious problem affecting numerouspeople, especially the young population who has made social networks andother internet contents a modus vivendi. A literature search was conducted forthe purpose of locating information on prevalence, diagnosis and treatmentof internet and computer addiction. Certain researchers and psychiatristsbelieve that the excessive internet use is a symptom of other disorders, suchas depression and anxiety, or impulse control disorder. However, over thepast few years a consensus has been reached that this constellation of symptomsis actually an addiction disorder. The American Society of AddictionMedicine (ASAM) has recently come up with a new definition, according towhich addiction represents a chronic brain disorder. Consequently, the newAmerican Classification of Mental Disorders (DSM-V) has introduced thisform of addiction under the diagnostic category dubbed “cybernetic disorder”.The field of internet addiction is advancing rapidly through its officialrecognition as a separate and distinct addiction disorder. Some individualswith internet addiction are at significant risk and merit professional care andtreatment. There are several treatments available, but the primary preventionis the most effective intervention. Family practitioners and psychiatrists shouldbe taught to screen their patients for this disorder.
Keywords: addiction; computer; internet; treatment